2023
DOI: 10.3390/su15054494
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Building Green Performances Using Vertical Greening Systems: A Case Study in Changzhou, China

Abstract: The benefits of greening systems on buildings have been frequently examined using experimental methods. However, few studies have adopted dynamic monitoring of real operational buildings to quantify the effects of greening systems on multiple building green performance indexes, such as thermal comfort, indoor air quality, and energy consumption. In this study, a type of multi-in-one indoor environmental quality monitoring device was adopted for vertical greening systems in a green-certified building in Changzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The mechanisms and effectiveness of air biofiltration in GWS depend on a broad range of factors related to plant species, fertilizers, microbial community structure, air contamination load, airflow rate, environmental conditions (e.g., seasonal variations), and the GWS design [31][32][33][34]. Three groups of factors, i.e., the sorption capacity of ECP, the specific impact of plant species on the biofilm activity/metabolic diversity, and their ability to remove FA, were tested.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms and effectiveness of air biofiltration in GWS depend on a broad range of factors related to plant species, fertilizers, microbial community structure, air contamination load, airflow rate, environmental conditions (e.g., seasonal variations), and the GWS design [31][32][33][34]. Three groups of factors, i.e., the sorption capacity of ECP, the specific impact of plant species on the biofilm activity/metabolic diversity, and their ability to remove FA, were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in addition to enhancing outdoor thermal condition, previous studies revealed that green roofs and green walls can facilitate to reduce the energy consumption associated with building heating and cooling [44]. In Xiangtan, China, Yang et al [45] evaluated the impacts of vertical greenery and green roofs on the working temperature inside air-conditioned rooms. The results showed that the working temperature of rooms with vertical greenery systems and green roofs was lower than that of rooms without these systems.…”
Section: #8 Indoor Thermal Environmentmentioning
confidence: 99%
“…A study conducted by found that green facades can significantly reduce indoor levels of particulate matter (PM), which can pose serious health risks [31]. Furthermore, research by Yang et al ( 2023) indicated that green facades can reduce indoor concentrations of harmful gases such as nitrogen dioxide and sulfur dioxide [45].…”
Section: Impact Of Green Facades On Indoor Air Qualitymentioning
confidence: 99%